ANALISIS PERSEPSI TAMU YANG MENGINAP TERHADAP KUALITAS PELAYANAN PETUGAS KANTOR DEPAN DI HOTEL PANGERAN BEACH PADANG (STUDI KASUS TAMU PRIA DAN WANITA) - Hendra Rantius (Akademi Pariwisata Bunda Padang, Sumatera Barat, Indonesia, 2020)
Customer service is one of the company's competitive advantages in retaining customers or guests. Increasingly fierce business competition makes business people compete in service to their customers. To provide the best possible service to customers, it is necessary to understand how customer service techniques are. Every personnel at all levels in the company must understand exactly how to serve customers or guests. Basically, officers who work in this section must understand who their customers are, what their customers' needs are, and how to serve and provide satisfaction to customers.One of the keys to success in increasing sales is by interacting and establishing good relationships with guests, by providing satisfying service. Interacting can build opportunities to promote products, services and companies. However, it is not easy for the company to run it. Success in creating customer satisfaction really depends on the Guest Service Agent's skill level. The world of hospitality has a wide dimension. The scope that can be discussed can be from various aspects, one of which is the perception of guests towards the services provided, while service is an aspect that cannot be separated from the world of hospitality. Excellent service is one of the strategies in providing satisfaction to customers (guests) which is important in business competition. In determining the level of satisfaction, a customer (guest) often sees the added value of the product and the performance of the service received from a purchase process for a service or product.